No Taps, No Toilets: First Nations and the Constitutional Right to Water in Canada - Boyd, David (McGill Law Journal / Revue de droit de McGill, 2011)
In 1977, the Canadian federal government promised to provide reserves with water and sanitation services comparable to similarly situated non-Aboriginal communities. Despite some progress, thousands of First Nations people, living on reserves across Canada, still lack access to running water or flush toilets. The adverse health effects associated with inadequate water infrastructure include elevated rates of communicable diseases such as influenza, whooping cough (pertussis), shigellosis, and impetigo. Do First Nations have an enforceable constitutional right to water? This article suggests that they do, based on the right to life, liberty, and security of the person under section 7 of the Canadian Charter of Rights and Freedoms; the right to equality under section 15 of the Charter; and governments’ obligation to provide “essential public services of reasonable quality to all Canadians” under section 36 of the Constitution Act, 1982. The legal arguments available pursuant to these constitutional provisions are buttressed by Canada’s obligations pursuant to international human rights law.